Physical ground for radioactive waste transmutation facility using thermonuclear neutrons - Rudychev, Y.V.; Khazhmuradov, M.A.; Slabospitskiy, R.P. (Вопросы атомной науки и техники, 2009)
Two variants of radioactive waste transformation system using thermonuclear neutrons were considered. In one case transuranium elements and fission products are irradiated together and in second one they are irradiated separately. Advantages and disadvantages of each case were analyzed. Second variant was chosen. Physical basing of facility construction for radioactive waste elements transmutation using thermonuclear neutrons for such variant was developed.